Rehabilitation treatment in multiple sclerosis - Ciechanowska, Katarzyna; Roeske, Alicja (Journal of Education, Health and Sport, 2018)
Multiple sclerosis (Latin: sclerosis multiplex, SM) it is a chronic demyelinating disease, which requires a comprehensive and continuous physiotherapy By improving the complexity of therapy, the lifespan of patients with multiple sclerosis has been equal to the average life expectancy of a healthy individual. Rehabilitation in patients with multiple sclerosis must be a process in which there is collaboration between a physician, a nurse, and a physiotherapist and a psychologist. You should plan your treatment and prepare your treatment plan accordingly, taking into account your goals closer and further. In addition to pharmacotherapy (eg interferon treatment), many physical exercises and physical methods are employed that seek the patient's independence. Significant influence on the effectiveness of therapy is also its systematic and involvement of relatives.